Yttrium nitrate improves the longevity of campanula cut flowers through strengthening the enzymatic antioxidant system and maintaining water balance - Limin Wu; Ninghai Lu (Horticultural Science)
We explored the role of yttrium nitrate (Y(NO3)3) in extending the longevity of campanula cut flowers. The results showed that Y(NO3)3 significantly enhanced the enzymatic antioxidant system, including the superoxide dismutase, peroxidase, ascorbate peroxidase, dehydroascorbate reductase, monodehydroascorbate reductase, glutathione reductase, glutathione peroxidase, and glutathione S-transferase. In this way, Y(NO3)3 increased the DPPH scavenging activity and decreased the malondialdehyde content and electrolyte leakage, which implied that Y(NO3)3 strengthened the antioxidant capacity. Meanwhile, Y(NO3)3 significantly improved the production of the soluble sugars, proline, and soluble protein, relative water content, average fresh weight change rate, and average water balance value, which indicated that Y(NO3)3 could maintain the water balance. Besides, Y(NO3)3 dramatically increased the flower diameter and extended the longevity. Our current research demonstrated that Y(NO3)3 improved the longevity by reinforcing the enzymatic antioxidant system and water balance, which added new information and a supportive base for the utilisation of Y(NO3)3 in the preservation of campanula cut flowers.